FROM THE HISTORY OF MATHEMATICS TEACHING METHODOLOGY - Umarova Matlyuba Yusufjanovna (Journals Park Publishing, 2022)
The article talks about the methodology of teaching mathematics and its history. In order to reveal the topic of the article, the scientific developments of scientists who conducted scientific research on this topic were used.
Keywords: mathematics, education, metohodology, school, mathematical education.